Evaluation of maize genotypes for resistance to fall armyworm under natural infestation conditions - Bhandari, Ghana Shyam; Bhandari, Priyanka; Sah, Lalit (Nepal Agriculture Research Journal, 2025)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), is one of the most significant invasive insect pests of maize in Nepal. Host plant resistance is a cost-effective, ecologically sustainable, and stable approach to reducing fall armyworm damage. This study aimed to identify maize genotypes that exhibit resistance or tolerance to fall armyworm damage in the Nepalese context. Total thirty-seven maize genotypes were screened for resistance to fall armyworm at the research field of the National Maize Research Program, Chitwan, Nepal, during the winter seasons (September/October–February/March) of two consecutive years, 2020 and 2021. The maize genotypes were evaluated using a randomized complete block design with three replications. Data were collected on foliar damage at the knee-high stage (V6 stage), before the tasseling stage (V12 stage), ear damage, and yield losses measured after harvesting. Statistically significant differences were observed among genotypes for ear damage score, cob length, cob diameter, thousand-grain weight, and grain yield, whereas leaf damage score did not show significant variation. None of the genotypes were found to be completely resistant or tolerant to fall armyworm in this study. However, Arun-3, SO1STYQ, Posilo makai-2, S0128, R-POP-2, BGBYPOP, Mankamana-3, Manakamana-7, RML86/RML96, Rampur hybrid-10 and CAH 1715 were identified as less susceptible to fall armyworm. These genotypes can be utilized as parents or sources of resistance in breeding programs. Grain yield exhibited a strong negative correlation with ear damage score (−0.529) and a weaker negative correlation with leaf damage score (−0.216), indicating that damage significantly reduces yield, particularly due to ear and leaf damage.